SETD2 drives METTL14-mediated m6A to suppress Piezo1 Attenuation and activate TGM2 to promote pulmonary hypertension - Shuai-shuai Zhao; Chuan Yuan; Jin-long Liu; Qi-cai Wu; Xue-liang Zhou (Cellular and Molecular Life Sciences)
Abstract Background Pulmonary arterial hypertension (PAH) is characterized by pathological vascular remodeling driven by pulmonary artery smooth muscle cell (PASMC) proliferation. While METTL14-mediated N6-methyladenosine (m6A) RNA modification has been implicated in PAH, the upstream regulators and downstream effectors linking m6A to PASMC dysregulation remain unclear. This study investigates the role of SETD2, a histone methyltransferase, in driving METTL14-dependent m6A modifications to promote PAH via Piezo1 and transglutaminase 2 (TGM2). Methods C57BL/6 mice were subjected to hypoxia, and pulmonary artery smooth muscle cells (PASMCs) were periodically stretched to establish PAH models in vivo and in vitro. The epigenetic regulation of METTL14 by SETD2-mediated H3K36me3 was investigated by chromatin immunoprecipitation (ChIP). Methylated RNA immunoprecipitation sequence (MeRIP-seq), RNA-seq, and dual-luciferase reporter gene data were used to determine whether METTL14 enhances the expression of Piezo1 in an m6A-dependent manner. To analyze comparisons between multiple datasets, one-way ANOVA was used. Results METTL14 overexpression increased PASMC proliferation by 1.45-fold (vs. controls) and elevated global m6A levels by 1.73-fold in total RNA and 1.43-fold in poly A + RNA. SETD2-driven H3K36me3 histone modification upregulated METTL14 expression by 1.76-fold, amplifying m6A deposition. In hypoxia-induced PAH mice, METTL14 overexpression exacerbated hemodynamic severity, increasing right ventricular systolic pressure (RVSP) by 29% and mean pulmonary arterial pressure (mPAP) by 33% (vs. hypoxia alone). SETD2 knockout in PASMCs reduced RVSP by 24%, mPAP by 28%, and pulmonary artery media thickness (PAMT) by 29%, while decreasing m6A levels by 48%. Piezo1 mRNA stability increased by 2.36-fold via METTL14-mediated m6A modification at adenosine 1080, elevating Piezo1 protein expression by 3.58-fold in PASMCs. Piezo1 overexpression increased intracellular Ca²⁺ influx, driving TGM2 activity by 1.79-fold and restoring PASMC proliferation despite SETD2 deficiency. Conclusions This study identifies a novel SETD2/H3K36me3/METTL14/m6A axis that stabilizes Piezo1 mRNA, promoting Ca²⁺-dependent TGM2 activation and PASMC proliferation in PAH. Targeting this pathway—via SETD2, METTL14, or Piezo1 inhibition—may offer therapeutic potential to ameliorate vascular remodeling in PAH.